Experimental realization of a thermal squeezed state of levitated optomechanics - Rashid, Muddassar; Tufarelli, Tommaso; Bateman, James; Vovrosh, Jamie; Hempston, David; Kim, M. S.; Ulbricht, Hendrik (American Physical Society, 2016)
We experimentally squeeze the thermal motional state of an optically levitated nanosphere by fast switching between two trapping frequencies. The measured phase-space distribution of the center of mass of our particle shows the typical shape of a squeezed thermal state, from which we infer up to 2.7 dB of squeezing along one motional direction. In these experiments the average thermal occupancy is high and, even after squeezing, the motional state remains in the remit of classical statistical mechanics. Nevertheless, we argue that the manipulation scheme described here could be used to achieve squeezing in the quantum regime if preceded by cooling of the levitated mechanical oscillator. Additionally, a higher degree of squeezing could, in principle, be achieved by repeating the frequency-switching protocol multiple times.